Common childhood symptoms and rural home-treatment practices - Onyiriuka, AN; Francisca, EN (Journal of Institute of Medicine Nepal, 2013)
Introduction: At home, mothers are usually the first to identify symptoms in their children and initiate treatment but there is paucity of information on these initial steps taken by these mothers. The objective of the study is to examine how mothers treat common childhood symptoms at home before presentation in the hospital. Methods: A hospital-based cross-sectional study along with a structured interviewer- administered questionnaire was used for data collection from 307 consecutive mothers. Data obtained included their children’s presenting symptoms, drugs administered, dosage regimen, source of the drugs, person who prescribed the drugs and storage of drugs. The axillary temperature of all the children were measured, using a mercury thermometer with the arm held firmly to the body. Results: Fever either alone or in association with other symptoms was the commonest (75.6%) presenting symptom. Among the 232 children reported as feverish by their mothers, 119 (51.3%) had normal body temperature (<37.50C) while the remaining 113 (48.7%) had elevated axillary temperature equal or greater than 37.50C. Analgesics, antimalarials and antibiotics were the three leading classes of drugs administered by the mothers, together accounting for 62.3% of all drugs. Antimalarials was the class of drug whose dosage regimen was most frequently incorrect, being correct in only 21.4% of cases. Mothers and patent medicine dealers accounted for 67.4% of all the prescriptions. The principal source of drugs was the patent medicine stores (62.2%). Of the 307 mothers, 64 (20.8%) administered left over drugs prescribed for a previous ailment. These drugs were stored mostly in closed cupboards and drawers (67.2% of cases) for a period of three to eight weeks (mean 5.2+0.8 weeks). The mothers had difficulty in correctly identifying fever with 51.3% of cases reported as feverish by their mothers having normal axillary temperature. Conclusions: The present home-treatment practices by mothers regarding their children’s symptoms is greatly deficient. Intervention aimed at improving the situation should include teaching mothers how to give oral drugs correctly, treat local infections, feed and give fluids during illnesses as well as ways of recognizing signs indicating immediate return to the health facility. Training of patent medicine dealers on the basics of drug action is also essential. DOI: http://dx.doi.org/10.2126/joim.v35i1.8893 Journal of Institute of Medicine, April, 2013; 35:23-27